Disability, the media and the Paralympic Games - Jackson-Brown, Carolyn (Abingdon, Oxon ; New York, NY : Routledge, 2020)
This book focuses on the ground-breaking coverage of the London 2012 Paralympic Games by the UK's publicly owned but commercially funded Channel 4 network, coverage which seemed to deliver a transformational shift in attitudes towards people with disabilities. It sheds important new light on our understanding of media production and its complex interactions with sport and wider society. Drawing on political economy and cultural studies, the book explores why and how a marginalised group was brought into the mainstream by the media, and the key influencing factors and decision-making processes. Featuring interviews with key people involved in the television and digital production structures, as well as organisational archives, it helps us to understand the interplay between creativity and commerce, between editorial and marketing workflows, and about the making of meaning. The book also looks at coverage of the Rio Paralympics, and ahead to the Tokyo Games, and at changing global perceptions of disability through sport. This is fascinating reading for any advanced students, researchers, or sport management or media professionals looking to better understand the media production process or the significance of sport and disability in wider society.
Introduction -- Spectacles of otherness : media, sports and disability dilemmas -- Riskier representations : Channel 4's public service broadcast model -- Normalising disability : mega-event media parity for the 'superhuman' supercrips -- Reframing meanings : encoding disability across multiple TV programme formats -- Marketing parasports : media, cultural production, and branded authenticity -- Conclusion.
OCLC-licensed vendor bibliographic record.
Keywords: Television and sports -- Social aspects -- Great Britain; Channel Four (Great Britain); SPORTS & RECREATION / Sociology of Sports; SOCIAL SCIENCE / Media Studies